The Design of a Controlled-Release Polymer of a Phytopharmaceutical Agent: A Study on the Release in Different Ph Environments Using the Ultrafiltration Technique - Martin-Trasancos, R; Martin-Trasancos, R (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
A series of hydrophilic copolymers were prepared using 2-hydroxyethyl methacrylate (HEMA) and itaconic acid (IA) from free radical polymerization at different feed monomer ratios using ammonium persulfate (APS) initiators in water at 70 °C. The herbicide 2,4-dichlorophenoxy acetic acid (2,4-D) was grafted to Poly(HEMA-co-IA) by a condensation reaction. The hydrolysis of the polymeric release system, Poly(HEMA-co-IA)-2,4-D, demonstrated that the release of the herbicide in an aqueous phase depends on the polymeric system’s pH value and hydrophilic character. In addition, the swelling behavior (Wt%) was studied at different pH values using Liquid-phase Polymer Retention (LPR) in an ultrafiltration system. The acid hydrolysis of the herbicide from the conjugates follows a first-order kinetic, showing higher kinetic constants as the pH increases. The base-catalyzed hydrolysis reaction of the herbicide follows a zero-order kinetic, where the basic medium acts as a catalyst, accelerating the release rate of the herbicide and showing higher kinetic constants as the pH increases. The differences in the release rates found for the hydrogel herbicide at different pH values can be correlated with the difference in their swelling capacity, where the release rate generally increases with an increase in the swelling capacity from water solution at higher pH values. The study of the release process revealed that all samples in distilled water at a pH of 10 are representative of agricultural systems. It showed first-order swelling kinetics and an absorption capacity that conforms to the parameters for hydrogels for agricultural applications, which supports their potential for these purposes. © 2024 by the authors.
Keywords: polymeric controlled release system; herbicide 2,4 D; ultrafiltration system